2020
DOI: 10.1007/s11102-020-01089-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and costs among prolactinoma patients: a cross-sectional study and analysis of determinants

Abstract: Purpose Prolactinomas are the most prevalent functioning pituitary adenomas. They affect gonadal function as well as health-related quality of life (HRQoL). This study aimed to report healthcare utilization and costs, including their determinants, for prolactinoma patients. Methods Cross-sectional study of 116 adult prolactinoma patients in chronic care in a Dutch tertiary referral center. Patients completed four validated questionnaires, assessing healthcare utilization and costs over the previous 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…[61] Interestingly, tumor size and prolactinoma treatment were however not significantly associated with healthcare utilization [61]. In addition, treatment costs were not significantly higher for patients with a macroprolactinoma, except in terms of medication costs [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[61] Interestingly, tumor size and prolactinoma treatment were however not significantly associated with healthcare utilization [61]. In addition, treatment costs were not significantly higher for patients with a macroprolactinoma, except in terms of medication costs [61].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that healthcare utilization and costs of patients treated for a prolactinoma are mainly associated with health-related quality of life. [ 61 ] Interestingly, tumor size and prolactinoma treatment were however not significantly associated with healthcare utilization [ 61 ]. In addition, treatment costs were not significantly higher for patients with a macroprolactinoma, except in terms of medication costs [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the USA has a different healthcare system than most European countries (52). European economic evaluations, reported lower annual direct costs of €8000-12000 (17,29,53) for patients with acromegaly (17,18,29,54), €2000 for prolactinoma (20) and €3000 (19) for NFA. However, these studies included yearly chronic care instead of the year of surgical intervention associated with a peak in costs (18)(19)(20)(21)26).…”
Section: Healthcare Costs In Perspectivementioning
confidence: 99%
“…Previous cost evaluation studies in pituitary healthcare were limited to the surgical procedure (12), index hospitalization (12)(13)(14), complications or readmissions (15,16), instead of encompassing the entire perioperative trajectory. Other studies focussed on a single diagnosis, limiting comparisons between pituitary tumour types and other case mix variables and prohibiting evaluation of the care pathways and the required capacity within the pituitary healthcare team (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Moreover, many studies assessed predictors of healthcare costs instead of cost determinants (24,28) with predictors not being cost drivers per se.…”
Section: Introductionmentioning
confidence: 99%